Dampak Hukum Serta Alasan Masyarakat Mempertahankan Tradisi Molas Kole terhadap Perempuan Pelaku Persinahan di Kabupaten Manggarai Barat - Kristoforus Adan Daman; Rudepel Petrus Leo; Orpa G. Manuain (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The purpose of this research is to analyze the legal impact and reasons for the community to maintain the Molas Kole tradition against women who commit adultery in West Manggarai Regency. The type of research used by researchers in conducting this research is empirical research translated by legal research complemented by empirical data. The results show that the legal impact of the Molas Kole Teradition is also very large. In addition to the impact on women on children, and the impact of this one customary law also has an impact on the family. The reason for the community to maintain this tradition is also irrelevant because when maintaining a customary crime which in its resolution has many losers, this custom can no longer be used as a way out in solving problems in society. The holding of this Customary Law Tradition is also contrary to church law, because many perpetrators of the Molas Kole tradition separate themselves from their husbands or wives and remarry without being known by the church, so that it will cause new problems that can ensnare the two perpetrators and even the family will also be involved.